Study of some physical properties for new materials for nonlinear optics - AMEUR, Anfal Saida; Lagoun, Brahim; Guibadj, Abdenacer (Université de Laghouat , Bibliothèque centrale, 2021)
It is well known that the DFT approaches have the ability to accurately predict the ground-state properties of the materials, and the developed analysis tools are vital to investigating their intrinsic mechanism. According to the noncentrosymmetric classes 2mm, I4 ̅, and 3m. In this study, the linear and nonlinear optical properties are investigated and analyzed using the density functional theory by full-potential linearized augmented plane wave (FP-LAPW) and plane wave pseudo-potential (PP-PW). The FP-LAPW method is used to study the electronic properties and linear optical properties with the recently developed density functional of Tran and Blaha. Furthermore, optical features such as dielectric functions, absorption coefficient, refractive index, reflectivity, and electron energy loss function are calculated for photon energies up to 40 eV. The elastic constant, nonlinear optical (NLO), linear electro-optical, and piezoelectric tensor within the framework of the modern theory of polarization and density functional perturbation theory (DFPT) are studied by the PP-PW approximation. Based on the semi-empirical relations, Young's modulus, shear and bulk modulus, Poisson's ratio, anisotropic factors, sound velocities, and Debye temperature.